Analisis keterikatan kerja ditinjau dari efikasi diri dengan dukungan organisasi sebagai variabel mediator pada pegawai perguruan tinggi di Surabaya (Faculty of Psychology, Universitas 17 Agustus 1945 Surabaya, 2021)
Higher Education Employees, especially Educational Personnel, are one of the most valuable human resource assets and have a vital role as a driving force for activities in Higher Education. One of the things that will improve their performance is seeing their engagement work. For this reason, this study was prepared with the aim of analyzing the relationship between employee self-efficacy and work involvement through organizational support as a mediator variable at one university in Surabaya. The sample used in this study were 212 employees at one university in Surabaya. The data analysis method used path analysis through Jeffrey's Amazing Statistics Program (JASP) software version 0.14.1.0. Through the research conducted, it is known that there is a significant positive relationship between self-efficacy and work involvement. The results of the data analysis of the correlation between self-efficacy and work involvement through organizational support as a mediator variable, obtained an estimated value = 0.012, coefficient z = 3.711 (z> 1.96) at p = 0.001 (p < 0.05). This shows that there is a relationship between self-efficacy and work involvement through organizational support as a significant mediator variable. Therefore, it can be concluded that there is a relationship between self-efficacy and work involvement through organizational support as a mediator variable for employees of one of the universities in Surabaya.